If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(x + 3y + 4z) = 0 (x * 9x + 3y * 9x + 4z * 9x) = 0 Reorder the terms: (27xy + 36xz + 9x2) = 0 (27xy + 36xz + 9x2) = 0 Solving 27xy + 36xz + 9x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9x'. 9x(3y + 4z + x) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3y + 4z + x)' equal to zero and attempt to solve: Simplifying 3y + 4z + x = 0 Reorder the terms: x + 3y + 4z = 0 Solving x + 3y + 4z = 0 Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. x + 3y + -3y + 4z = 0 + -3y Combine like terms: 3y + -3y = 0 x + 0 + 4z = 0 + -3y x + 4z = 0 + -3y Remove the zero: x + 4z = -3y Add '-4z' to each side of the equation. x + 4z + -4z = -3y + -4z Combine like terms: 4z + -4z = 0 x + 0 = -3y + -4z x = -3y + -4z Simplifying x = -3y + -4zSolution
x = {0, -3y + -4z}
| 5(7x+9)=-130 | | 2x^2=2500 | | -9(5d-8)= | | .50(40)=.20(40-m)+.80m | | 8y+5=24+2y | | 4a+b=20 | | -13x+21x+2x+15=-45 | | -16k+33k-80k+76k=-52 | | 3a+b=15 | | x^2+-2x-5.25=0 | | x^2+-2x-5.25=0 | | -4x+3(2x-1)=-5 | | 3(2x-4)=2(2x-10) | | 9-(-5+x)-7x=50 | | 5x+6+5=2 | | 3x+2a=2a+24 | | 114s+14s+12s=1 | | 2x^2-10x^2+9x= | | 4x+(x-5)(x+4)+15=(3-x)(x+3)+(x+6)(x-3) | | 2a^2-18a+20.25=0 | | x-3(17)=81 | | F(X)=(32-x)(40-x) | | x+2=5x+22 | | 2kx^2+kx-x=0 | | 3X+1=48 | | 4x+y=-x+9 | | 2x+3=61 | | 6(-2-9k)= | | 3x-1.66=-7(3.5x-3)-3 | | 2(6+5x)=102 | | 4x=81+x | | -29x+6.1=-5(5.8x+2.2)-0.3 |